2021
DOI: 10.1021/acs.jpca.1c02000
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Potentials for a Lattice-Mapped Coarse-Grained Scheme

Abstract: The conservative potential, arising from a coarse-grain (CG) mapping scheme for nonbonded atomistic particles, is studied. This is a bottom-up approach from first-principles that maps atomistic particles to fluid element-like subcells whose centers lie on a regular, cubic lattice. Unlike standard CG mapping schemes, the current one uses dynamic labeling which on-the-fly changes the CG labels of the particles. The subcells can also be different sizes and shapes, in principle. Equilibrium atomistic molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 38 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…Recently, a “dynamic mapping” scheme was developed by mapping velocities instead of configurations, which only requires the initial configuration from smoothed centroidal Voronoi tessellations . To note, this mapping scheme is based on a Lagrangian description to track individual fluid particles, but a complementary Eulerian description can also be established in a similar vein . In turn, this new approach allows stable propagation of the CG blobs over time, indicating its applicability to various fluids, e.g., heterogeneous multiphase systems.…”
Section: Basics Of Bottom-up Coarse-grained Modelingmentioning
confidence: 99%
“…Recently, a “dynamic mapping” scheme was developed by mapping velocities instead of configurations, which only requires the initial configuration from smoothed centroidal Voronoi tessellations . To note, this mapping scheme is based on a Lagrangian description to track individual fluid particles, but a complementary Eulerian description can also be established in a similar vein . In turn, this new approach allows stable propagation of the CG blobs over time, indicating its applicability to various fluids, e.g., heterogeneous multiphase systems.…”
Section: Basics Of Bottom-up Coarse-grained Modelingmentioning
confidence: 99%
“…Lynn and Thachuk derived the coarse-grain (CG) equations of motion (EoM) for a general, lattice-like mapping scheme using Mori–Zwanzig (MZ) theory. , Such an approach produces dynamically correct EoM because MZ theory is simply a way to partition the Liouville operator in the evolution equations of dynamical variables. Luo and Thachuk studied the behavior of the conservative terms in this CG EoM using a Heaviside switching function . They found that the CG potential has a quadratic form whereas the effect of particles crossing subcell boundaries shows up as linear correlations between CG variables .…”
Section: Introductionmentioning
confidence: 99%
“…Luo and Thachuk studied the behavior of the conservative terms in this CG EoM using a Heaviside switching function . They found that the CG potential has a quadratic form whereas the effect of particles crossing subcell boundaries shows up as linear correlations between CG variables . The CG diagonal mass elements are discrete, but their distributions can be described by a multivariate Gaussian .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations